Sistem Informasi Pengelolaan Data Inventarisasi Barang Pada Kantor Kecamatan Dusun Utara Kabupaten Barito Selatan - Agung Prabowo; Arliyana Arliyana; Jhonyver Jhonyver (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The data collection of inventory items carried out at the North Dusun District Office in South Barito Regency uses the Microsoft Word application in the Microsoft Office application. Data collection in this way takes a lot of time when making reports when needed. With the existence of these problems, the writer will discuss them in this final project research. By taking the title